Juridical Analysis Of The Delegation Of Authority Of Doctors To Nurses In Health Services At Health Centers - Maya Santika; Rokhmat Rokhmat; Efrila Efrila; Sutrisno Sutrisno (JURNAL HUKUM SEHASEN, 2024)
This study aims to analyze the juridical aspect of the delegation of authority from doctors to nurses in health services in health centers. Delegation of authority is an important process in the implementation of health services, especially in health centers, which often face limited human resources. This study uses a normative approach by analyzing applicable laws and regulations, including the Medical Practice Law, the Nursing Law, and other related regulations. The results of the study show that the delegation of authority from doctors to nurses must be based on clear and specific legal provisions to ensure the legality and safety of patients. Complete and accurate documentation of the patient's medical record is essential to maintain transparency and accountability in the delegation of authority process. In addition, the delegation of authority must be carried out by considering the competence and qualifications of nurses, and accompanied by adequate supervision from the doctor who provides the authority. This study concludes that although delegation of authority is a common and necessary practice in health services in Puskesmas, its implementation must be strictly regulated and supervised to ensure that the health services provided remain in accordance with professional standards and applicable laws.